Are all individual investors equally prone to the disposition effect all the time? New evidence from a small market - Leal, Cristiana Cerqueira (2010)
This paper investigates the disposition effect on the Portuguese stock market, on the basis of a unique database that consists of trading records of 1496 individual investors. We found strong evidence of the disposition effect, studied on the basis of trades, volume and value traded. This preference for realizing gains to losses was observed every month of the year and globally for all individual investors. Even at the end of the fiscal year, the disposition effect still holds, as opposed to the evidence found in other markets. We also studied the disposition effect related to market tendency. By dividing the data period into a bull and a bear period, we found evidence of disposition effect for both periods, but with differences in terms of its intensity. In the bull market period, the disposition effect is even more evident than in the bear market. We believe these results can be explained with behavioral reasons. We also investigated the disposition effect related to proxies of investors' sophistication. We divided investors on the basis of the trading frequency, volume of transactions and portfolio value and found evidence that investors in the higher percentiles are less prone to the disposition effect than the ones in the lower percentiles, even though both exhibit evidence of this effect.